2015
DOI: 10.1080/10408398.2013.772090
|View full text |Cite
|
Sign up to set email alerts
|

Biological Activities of Red Pepper (Capsicum annuum) and Its Pungent Principle Capsaicin: A Review

Abstract: Capsaicin, the pungent alkaloid of red pepper (Capsicum annuum) has been extensively studied for its biological effects which are of pharmacological relevance. These include: cardio protective influence, antilithogenic effect, antiinflammatory, and analgesia, thermogenic influence, and beneficial effects on gastrointestinal system. Therefore, capsaicinoids may have the potential clinical value for pain relief, cancer prevention and weight loss. It has been shown that capsaicinoids are potential agonists of cap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
208
0
11

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 340 publications
(221 citation statements)
references
References 89 publications
2
208
0
11
Order By: Relevance
“…According to a report by Okumura, Tsukui, Hosokowa, and Miyashita (2012), the antidiabetic activities of capsaicin and caffeine on the blood glucose level of obese/diabetic model mice were found to be high in KK‐A(y) obese/diabetic mice. Recently, Srinivasan (2016) has reported that capsaicin as natural anti‐inflammatory compounds was effective as indomethacin (a nonsteroidal anti‐inflammatory drug) in suppressing aberrant crypt foci in rat.…”
Section: Potentials Of Chili (Capsicum Annuum) In Alleviating Micronumentioning
confidence: 99%
“…According to a report by Okumura, Tsukui, Hosokowa, and Miyashita (2012), the antidiabetic activities of capsaicin and caffeine on the blood glucose level of obese/diabetic model mice were found to be high in KK‐A(y) obese/diabetic mice. Recently, Srinivasan (2016) has reported that capsaicin as natural anti‐inflammatory compounds was effective as indomethacin (a nonsteroidal anti‐inflammatory drug) in suppressing aberrant crypt foci in rat.…”
Section: Potentials Of Chili (Capsicum Annuum) In Alleviating Micronumentioning
confidence: 99%
“…Despite the irritation of the pepper causing unusual reactions, elephants eat mango fruits coated with the chilli pepper concentrate. Capsaicin from chilli pepper has dose-dependent effects (Ameh et al, 2015;Srinivasan, 2016). The elephant's willingness to eat fruits coated with chilli pepper during this trial might be due to the amount of the chilli pepper which was coated on fruits while plunging them in the concentrate, and which had not enough strong repellent effect on elephants.…”
Section: Discussionmentioning
confidence: 95%
“…The greatest unusual reactions recorded at site S3 indicates that elephants might have been deterred with a stronger concentrated chilli pepper. Yet, the use of a more concentrated chilli pepper raises concerns about lethal effects of capsaicin (Ameh et al, 2015;Srinivasan, 2016). Capsaicin effects are also known to decrease as consumers become habituated (Srinivasan, 2016) explaining why elephant were less willing to eat mongo fruits coated with chilli pepper the first trial day compared to the other days.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations